Chlorophyll biosynthesis under the control of arginine metabolism - Kiss, Éva; Talbot, Jana; Adams, Nathan B P; Opekar, Stanislav; Moos, Martin; Pilný, Jan; Kvasov, Tatjana; Schneider, Emilia; Koník, Peter; Šimek, Petr; Sobotka, Roman (Cell reports, 2023)
In natural environments, photosynthetic organisms adjust their metabolism to cope with the fluctuating availability of combined nitrogen sources, a growth-limiting factor. For acclimation, the dynamic degradation/synthesis of tetrapyrrolic pigments, as well as of the amino acid arginine, is pivotal; however, there has been no evidence that these processes could be functionally coupled. Using co-immunopurification and spectral shift assays, we found that in the cyanobacterium Synechocystis sp. PCC 6803, the arginine metabolism-related ArgD and CphB enzymes form protein complexes with Gun4, an essential protein for chlorophyll biosynthesis. Gun4 binds ArgD with high affinity, and the Gun4-ArgD complex accumulates in cells supplemented with ornithine, a key intermediate of the arginine pathway. Elevated ornithine levels restricted de novo synthesis of tetrapyrroles, which arrested the recovery from nitrogen deficiency. Our data reveal a direct crosstalk between tetrapyrrole biosynthesis and arginine metabolism that highlights the importance of balancing photosynthetic pigment synthesis with nitrogen homeostasis.
Keywords: dusík; ornithin; arginin; Synechocystis; chlorofyl; Arginine; Ornithine; arginine metabolism; genome-uncoupled-4; tetrapyrrole biosynthesis; chlorophyll; Nitrogen; nitrogen homeostasis; Chlorophyll; CP: Plants; bilins